2023
DOI: 10.3390/antibiotics12060993
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Important Genetic Factors for Growth during Cefotaxime-Gentamicin Combination Treatment in blaCTX-M-1 Encoding Escherichia coli

Abstract: Due to the rapid spread of CTX-M type ESBLs, the rate of resistance to third-generation cephalosporin has increased among Gram-negative bacteria, especially in Escherichia coli, and there is a need to find ways to re-sensitize ESBL E. coli to cephalosporin treatment. A previous study showed that genes involved in protein synthesis were significantly up-regulated in the presence of subinhibitory concentration of cefotaxime (CTX) in a CTX-M-1-producing E. coli. In this study, the interaction between CTX and gent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Genes categorized as ‘essential’ in TraDIS are either essential for survival or their interruption is associated with a severe fitness-cost under the given conditions 40 . This number of ‘essential’ genes is in a similar range as previously published counts of ‘essential’ genes in E. coli that were determined by TraDIS analysis 16 , 40 , which provides strong assurance in the quality of our Tn-libraries enabling us to obtain meaningful conclusions.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Genes categorized as ‘essential’ in TraDIS are either essential for survival or their interruption is associated with a severe fitness-cost under the given conditions 40 . This number of ‘essential’ genes is in a similar range as previously published counts of ‘essential’ genes in E. coli that were determined by TraDIS analysis 16 , 40 , which provides strong assurance in the quality of our Tn-libraries enabling us to obtain meaningful conclusions.…”
Section: Discussionsupporting
confidence: 73%
“…Deletion of the hflCK cluster confirmed that the cluster was indeed important for growth in the STREP and GEN-resistant background in the presence of the corresponding aminoglycosides. In previous studies, disruption of hflK (and hflC 30 ) has been associated with increased sensitivity to GEN in GEN-susceptible E. coli MG1655 30 , MG1655/pTF2 16 and E. coli BW25113 45 allowing us to confide in the reliability of our data.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations